Survey Applies Public Collection Development Librarians’ Support for Intellectual Freedom to Collection Process - Costello, Laura (Evidence Based Library and Information Practice, 2020)
A Review of: Oltmann, S. M. (2019). Important factors in Midwestern public librarians’ views on intellectual freedom and collection development: Part 2. The Library Quarterly, 89(2), 156-172. https://doi.org/10.1086/702203 Abstract Objective – To explore how librarian attitudes regarding intellectual freedom and demographic factors influence collection development decisions. Design – Online survey. Setting – Public libraries in the Midwestern United States. Subjects – 645 collection development library professionals employed in public libraries. Methods – An electronic survey was distributed to 3,018 public library directors in nine Midwestern states and completed by the library professional primarily responsible for collection development (Oltmann, 2019, p. 6). The survey had a 21.37% response rate. The survey focused on intellectual freedom in the management of collections and probed the participants for their experiences and influences in making collection development decisions. The survey also asked participants to make hypothetical purchasing and holdings decisions for library materials based on a short description of the material. Main Results – Participants indicated that they used a variety of different tools for the selection of materials including patron requests. Of the participants, 45.7% indicated that their library had a policy, practice, or metric to assess the balance of their collections, while 54.3% indicated that their libraries did not have policy or method in place for ensuring that their collection was balanced. Of the respondents, 73.4% felt that local community values should be considered in collection development decision, but 62.3% said that this should not be the most important factor in decisions. Overall, the political leaning of the community did not have an impact on participants’ alignment with the ALA's stances on intellectual freedom. Most respondents (73.4%) felt that government library funding bodies should have an influence over collection development decisions. Some respondents indicated they felt internal pressure from other library staff or the library board to purchase particular materials (28.1%) or relocate materials (14.1%). Respondents also indicated that they felt external pressure from their communities to purchase (32%) or restrict or withdraw (19.1%) materials. In the hypothetical purchasing scenario, most librarians indicated that they would purchase the majority of items. Some participants (39.8%) felt tension between their personal and professional views on intellectual freedom. Conclusion – The first part of this article found that holding an MLS degree had a significant impact on participants' stance on intellectual freedom and alignment with the American Library Association (ALA) principles. This part indicated that they also felt greater pressure to withdraw, acquire, and manage particular materials in their collections and felt more tension between their personal and professional stances on intellectual freedom. Age, gender, duration of work, and community political affiliations significantly impacted only some of the participants' responses. Overall, there was general support for intellectual freedom and alignment with the ALA principles; however, 40% of respondents indicated tension between their personal and professional beliefs about intellectual freedom.